The Influence of User Participation, Information Technology Sophistication and User Technical Capabilities on the Performance of the Accounting Information System at Hosana Lippo Cikarang Hospital - Setyawan, Wisnu; Wulandari, Siska (Journal of Economics, Management and Accounting (JEMA), 2024)
This study aims to determine the effect of user participation, information technology sophistication, and user technical capabilities on the performance of accounting information systems. The location of this research was conducted at Hosana Hospital Lippo Cikarang. The sample in this study consisted of 84 employees using accounting information systems who were selected using a saturated sampling technique from the entire population of employees at Hosana Lippo Cikarang Hospital. The data was obtained through a survey using a questionnaire and analyzed by the method of multiple linear analysis. The results show that partially, user participation has a positive and significant effect on the performance of accounting information systems and the technical ability of users has a positive and significant effect on the performance of accounting information systems. Simultaneously user participation, sophistication of information technology, and user technical ability affect the performance of accounting information systems.